Dialektika Teks Hadis dan Realitas Sosial: Transformasi Resepsi Hadis Ikhtilāṭ di Lembaga al-Jami UIN Alauddin Makassar - Muh. Rizaldi; A. Muh. Azka Fazaka Rif'ah; Anugrah Eran Batu; Muhammad Ilham Ulul Azmi Khasri (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2025)
The strictness of the issue of ikhtilāṭ as part of the culture of the da'wah institution has shifted among the activists of the da'wah al-Jami' UIN Alauddin Makassar campus. The pattern of interaction between men and women has changed from very strict to more relaxed. This paper aims to examine the transformation and reception of the hadiths of ikhtilāṭ among the campus da'wah activists of al-Jami' UIN Alauddin Makassar. In dissecting the research problem, this study uses the theory of reception and sociological knowledge developed by Karl Mannheim. The results of this study conclude that the transformation of the issue of ikhtilāṭ in the al-jami' campus da'wah institution is inseparable from the declaration of religious moderation that has taken root at UIN Alauddin Makassar. In the transformation process, two classifications were found as the triggers of their attitude shift. The 2006-2019 period is a phase that represents the strictness of the issue of ikhtilāṭ which is expressed through organizational policies, including: the mandatory use of hijab (curtain barrier), polarization of the board and polarization of the secretariat. While the 2020-2024 period represents an open attitude in the issue of khtilath by placing the law of khtilath situationally and conditionally (tawassuth). This transformation occurred as a logical consequence of the shift in the reception of the hadith of khtilath from a textual to a contextual understanding paradigm. The fundamental difference between the phases of the 2006-2019 period and the 2020-2024 period also affects the different dimensions of the meaning of ikhtilāṭ in the perspective of Mennheim's sociology of knowledge, be it in the realm of objective, expressive or documentary meaning.